Cooperative organocatalysis of Mukaiyama-type aldol reactions by thioureas and nitro compounds. Issue 48 (24th May 2016) - Bukhryakov, Konstantin V.; Desyatkin, Victor G.; Rodionov, Valentin O.
Abstract : A unique organocatalytic system for Mukaiyama-type aldol reactions based on the cooperative action of nitro compounds and thioureas has been identified. Abstract : A unique organocatalytic system for Mukaiyama-type aldol reactions based on the cooperative action of nitro compounds and thioureas has been identified. This system is compatible with a wide range of substrates and does not require low temperatures, inert atmospheres, or an aqueous workup. A catalytic mechanism based on nitro group-mediated silyl cation transfer has been proposed.